2016
DOI: 10.1186/s12936-016-1230-9
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of Plasmodium and absence of malaria transmission in Conakry, Guinea: prospects for elimination

Abstract: BackgroundOver the past 15 years, mortality and morbidity due to malaria have been reduced substantially in sub-Saharan Africa and local elimination has been achieved in some settings. This study addresses the bio-ecology of larval and adult stages of malaria vectors, Plasmodium infection in Anopheles gambiae s.l. in the city of Conakry, Guinea, and discusses the prospect for malaria elimination.MethodsWater bodies were prospected to identify potential mosquito breeding sites for 6 days each in the dry season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Yet members of An. gambiae complex were largely predominant in most urban settings [11,14,54,55]. This is in conformity with these species capacities to adapt to anthropogenic and/ or environmental changes and to feed exclusively on humans [56].…”
Section: Discussionsupporting
confidence: 69%
“…Yet members of An. gambiae complex were largely predominant in most urban settings [11,14,54,55]. This is in conformity with these species capacities to adapt to anthropogenic and/ or environmental changes and to feed exclusively on humans [56].…”
Section: Discussionsupporting
confidence: 69%
“…Almost half the children under the age of five were found to have had malaria and diarrhoea in their lifetimes as reported by their caretakers. In contrast, a desk review of ministry of health records in Conakry revealed malaria prevalence less than 10% in children under five between 2009 and 2012 [18]. The difference could be due to the fact that this survey was in a rural area which tends to have higher malaria prevalence compared to urban areas.…”
Section: Disease Burdenmentioning
confidence: 77%
“…We compared the performance of five adult trapping methods to determine mosquito species abundance and diversity in Maferinyah sub-prefecture, Guinea, and provide evidence towards the most suitable trap for surveillance. To our knowledge, only larval collections, pyrethroid spray catches, exit traps, aspirators, HLCs and LT have been used in Guinea to collect mosquitoes [16,19,[22][23][24]. In this study, we selected gravid traps (GT), Stealth traps (ST), LT and BG sentinel 2 traps (BG2T) with two different lures (BG and MB5) in comparison with HLCs to test new trapping methods not previously used in Guinea to capture the highest diversity of mosquito species.…”
mentioning
confidence: 99%